Efektivitas Hypnobirthing dalam Mengurangi Nyeri Punggung Bawah pada Wanita Hamil: Studi Quasi-Eksperimental - Murbiah; Santhna Letchmi Panduragan (Journal of Medical Practice and Research, 2025)
Low back pain (LBP) is one of the most common discomforts experienced by pregnant women, particularly in the third trimester. Despite its prevalence, non-pharmacological interventions targeting this specific issue remain underexplored. Hypnobirthing, a method involving relaxation, visualization, and self-hypnosis, has shown promise in reducing labor-related pain and anxiety, but its effectiveness in alleviating LBP during pregnancy is still unclear.  This quasi-experimental study aimed to evaluate the effectiveness of hypnobirthing techniques in reducing low back pain among pregnant women.  A quasi-experimental design was used involving pregnant women in their third trimester. Participants were divided into intervention and control groups. The intervention group received a structured hypnobirthing program for four weeks, while the control group received routine antenatal care. Pain intensity was measured using the Visual Analog Scale (VAS) before and after the intervention.  The hypnobirthing intervention group reported a statistically significant reduction in low back pain compared to the control group. Participants also reported improved relaxation and better coping mechanisms related to pregnancy discomfort. Hypnobirthing appears to be an effective complementary intervention for reducing low back pain in pregnant women. These findings support its integration into antenatal care programs and call for further research exploring its mechanisms and long-term benefits.